The US Great Plains, Change, and Place Development - Harrington, Lisa M.B. (CAB International, Wallingford, UK, 2009)
This chapter presents the changing conditions of a subregion and a specific place embedded within the larger region (space) of the Great Plains. From a general overview of the Great Plains, through a discussion of a portion of its High Plains subregion, and ending with a specific Kansas community, the focus is on general economic and environmental conditions. While some places within the larger space of the North American Great Plains/prairie region may find the wherewithal to succeed in the longer term—by capitalizing on local features and local entrepreneurial strength—these are likely to be exceptional in a large and relatively sparsely populated region.
Keywords: Great Plains; United States; Kansas; Livestock; Crops; Energy; Economic development